A Relation Shaped by Geopolitical Ambitions: The United States and Cambodia during the Cold War - Vibol Neak (IKAT: The Indonesian Journal of Southeast Asian Studies, 2019)
The diplomatic relation between the United States and Cambodia began during the Cold War, before Cambodia achieved independence from France in 1953. This article  examines the political constellation between the two states during the Cold War. The United States had been an ally and a firm supporter of Cambodia at certain times, while also being controversial enemies in other moments. The relationship worsened during the Cold War, and the two countries had gone from allies to enemies. It could be argued that the relationship deteriorated due to several reasons: the US’ foreign policy, which was crafted to contain communism, Cambodia’s failure to be truly neutral as it was often biased to the communist bloc, and the impact of third-party states.